The effectiveness of an education intervention to prevent chlamydia infection among Greenlandic youth. (February 2015) - Rink, Elizabeth; Montgomery-Andersen, Ruth; Anastario, Mike
The purpose of this study was to implement a sexual health behavioural intervention in Greenland in order to reduce sexually transmitted infection rates among a population of Greenland youth. This behavioural intervention was called Inuulluataarneq (Having the Good Life). Inuulluataarneq's objects included: (1) increase Greenlandic youth's overall knowledge about sexually transmitted infections and sexual health; (2) increase parent/guardian-youth communication about topics related to sexually transmitted infections and sex; and (3) increase consistent condom use among Greenlandic youth. We hypothesised that increased awareness of sexually transmitted infections and sexual health as well as increased communication between parents/guardians and their adolescent children would influence sexual risk behaviour and reduce sexually transmitted infections among our sample population, with a focus on urine samples of chlamydia infection. Results indicate that the influence of having a parent/guardian to speak with about topics related to sex, including the consequences of pregnancy, are key protective factors in reducing sexually transmitted infections among Greenlandic youth. Inuulluataarneq demonstrates that intensive short-term education and skill-building delivered by a trained community member is an effective sexually transmitted infection prevention intervention method among young Inuit populations who live in small isolated Arctic communities.